Possibility Theorems with Interpersonally Comparable Welfare Levels - Roberts, Kevin W. S. (Review of Economic Studies, 1980)
Journal Article Possibility Theorems with Interpersonally Comparable Welfare Levels Get access Kevin W. S. Roberts Kevin W. S. Roberts Massachusetts Institute of Technology and St. Catherine's College, Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 47, Issue 2, January 1980, Pages 409–420, https://doi.org/10.2307/2297001 Published: 01 January 1980 Article history Received: 01 April 1976 Accepted: 01 January 1978 Published: 01 January 1980